Confirmatory Factor Analysis of a Scientific Imagination Assessment for the Bohr Atomic Model - Fifin Dewi Ratnasari; Masturi Masturi; Suharto Linuwih; Ani Rusilowati; Endang Susilaningsih; Dwi Yulianti (FKIP Universitas Lampung, 2026)
The scientific imagination is not merely a source of daydreaming and creativity; it helps define, build, and apply scientific models, conduct scientific tests, develop scientific theories, and advance scientific knowledge and concepts. The focus of this study was to develop an instrument to evaluate students' scientific imagination as they explore the Bohr atomic model and to validate it through CFA. A research and development methodology was employed, with 101 students enrolled in the physics program at Universitas Negeri Semarang (UNNES) who had previously completed coursework on the Bohr model. The validity of the instrument developed for this purpose was established with confirmatory factor analysis (CFA). Descriptive analysis was conducted to profile physics students' abilities in scientific imagination when analyzing the Bohr atomic model. The findings of this study demonstrated that the scientific imagination assessment had acceptable validity and reliability based on the following parameters: comparative fit index (CFI) of 0.967, Tucker-Lewis index (TLI) of 0.957, root mean square error of approximation (RMSEA) of 0.060, standardized root mean square residual (SRMR) of 0.051, and goodness of fit index (GFI) of greater than 0.978. Scientific imagination can be divided into two dimensions: creative imagination and reproductive imagination. Creative imagination is divided into five sub-dimensions: intuition, sensitivity, productivity, exploration, and novelty. Reproductive imagination is divided into five sub-dimensions: focus, effectiveness, transformation, crystallization, and dialectics. This research successfully developed and validated a Scientific Imagination Assessment (SIA) instrument specifically designed to measure students' scientific imagination in the context of abstract physics, specifically the Bohr atomic model. This instrument employs a structured, essay-based assessment scored on a 5-point Likert scale, enabling it to capture students' cognitive and representational processes in greater depth. Keywords: CFA, scientific imagination assessment, bohr atomic model.